A kohéziós politika új dimenziói a 2014–2020-as időszakban - Sarudi, Csaba; Bertalan, Péter (Acta Scientiarum Socialium, 2015)
New Dimensions of Cohesion Policy in the 2014–2020 Period. According to the EU budget for 2014-2020 the cohesion policy invests 325 billion euros in member states in order to be able to accomplish the aims related to growth and the creation of workplaces and deal with the challenges of climate change, energy dependency and social exclusion. The smart, sustainable and inclusive growth should be highlighted from the strategic objectives of cohesion policy and the 11 thematic objectives, the accomplishment of which is compulsory for all the member states. The template requirement of the implementation of EU goals makes it difficult to enforce national aims and their representation in development plans. Another problem is that among the goals there are no specifically regional ones. The most important regulatory changes in the new budget cycle refer to the reduction of utilizable funds, strengthening resource and thematic concentration, stricter measurement of results, and making it more difficult to access funds. The system of aims of the Széchenyi 2020 development plan is adjusted to the regulations following the value aims of Europe 2020 strategy and formulates sustainable, high added value production, expansion of employment and national aims promoting economic growth. The 8 cohesion programs including the national contribution envisage the use of 25297 billion euros, the 35 percent of which serves the goals of economic development. Priority is given to regional and municipal development, environmental and energy efficiency, traffic and human resource development. In the paper we deal with the changes and strategy of cohesion policy and the Széchenyi 2020 development plan. We evaluate the development possibilities regarding self-governments, the decentralization of funds and new regional integration tools. Hungary meets the EU requirements in the 7 year period starting in 2014, and takes one of the most advantageous net positions in the ranking of EU 28.